ANALISIS DAMPAK EKONOMI PETERNAKAN SUSU KAMBING ETAWA TERHADAP MASYARAKAT LOKAL DI KECAMATAN TAMBANG KABUPATEN KAMPAR (STUDI KASUS PETERNAKAN FATHUR FARM) - Muhammad Fathur Rizqi.A; Deny Setiawan; Indri yovita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2026)
This study aims to determine the economic impact of Fathur Farm's Etawa goat dairyfarming. In this study, the researcher conducted an analysis related to several variables thatinfluence the economic conditions of the community in Tambang District. The theory used inthis study is income theory. The research method used is descriptive quantitative research.The population in this study consisted of 507 people classified as Etawa goat breeders, dairyworkers/processors, and the community around the farm. Meanwhile, the sample was takenusing a simple random sampling technique using the Slovin formula with a tolerance limit of10% of 84 research respondents. The data collection technique used was a questionnairedistributed directly to the research respondents. The results of the study showed that thecommunity agreed that Fathur Farm provides increased income to the community, such asproviding monthly income and meeting the community's needs, both daily needs and schoolneeds of family members. Fathur Farm also provides opportunities and job opportunities forthe community by becoming employees or working as sellers and agents of livestockproducts.. Keywords: Economic Impact Analysis, Increased Community Income and Employment,Fathur Farm